2000
DOI: 10.1017/s0252921100056669
|View full text |Cite
|
Sign up to set email alerts
|

Selfconsistent Models of Winds from Rotating Early-Type Stars – Application to B[e] star winds

Abstract: Abstract. We present results of 2.5-D radiation hydrodynamical simulations of winds from rapidly rotating stars. For the first time, we consider the dependence of the line statistics on local density and radiation temperature implying a spatial variation of the force-multiplier parameters k, a and S which control the dynamics of the flow. We apply our models to the problem of disk formation in B[e]-star winds. Winds from rotating early-type starsIn recent years, the actual structure of radiation driven winds f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 6 publications
2
29
0
Order By: Relevance
“…However, with an initial rotation of 410 km s −1 the models predict that the star can reach high abundances while still keeping the high rotational velocity. This is therefore consistent with the above hypothesis that GHV-62024 is a fast rotator seen from a low inclination angle, whose velocity field properties would have been modified towards high β values without modifying the average WLR (in agreement with Maeder 2001 andPetrenz &.…”
Section: Discussionsupporting
confidence: 90%
“…However, with an initial rotation of 410 km s −1 the models predict that the star can reach high abundances while still keeping the high rotational velocity. This is therefore consistent with the above hypothesis that GHV-62024 is a fast rotator seen from a low inclination angle, whose velocity field properties would have been modified towards high β values without modifying the average WLR (in agreement with Maeder 2001 andPetrenz &.…”
Section: Discussionsupporting
confidence: 90%
“…Feldmeier et al 1997;Runacres & Owocki 2002), and of effects of stellar rotation on the stellar wind (cf. Petrenz & Puls 2000) showed that basic wind parameters (i.e. terminal velocity and mass-loss rate) can be well reproduced by stationary and spherically symmetric wind models (for rotational velocities lower than the critical rotational velocity).…”
Section: Discussionmentioning
confidence: 96%
“…Such a method was used for the investigation of stellar wind structure, particularly in 2D, e.g. by Owocki et al (1994) and Petrenz & Puls (2000). Another method (integral method) was developed by Beutler (1979) and was applied to a solar wind problem by Bürgi (1992).…”
Section: Methodsmentioning
confidence: 99%